Eruptive Seborrheic Keratoses Restricted to Plaque/Patch-Stage Mycosis Fungoides - Eve Lebas; Pascale Quatresooz; Jorge E. Arrese; Arjen F. Nikkels (Karger Publishers, 2017)
Eruptive seborrheic keratoses (ESK) are rare in dermatology. They are usually inflammatory in nature and may be encountered as Leser-Trélat sign. ESK may also be simultaneously observed with hepatic angiomas, chemotherapy, segmental neurofibromatosis, HIV or erythrodermic pityriasis rubra pilaris, psoriasis, and drug eruption. ESK may be transient and self-healing. Others recede after successful treatment of the underlying disease. In some instances, seborrheic keratoses may follow an isotopic response and remain strictly restricted to sites of previous eczema, photo-exposition or tattoos. A patient with patch/plaque lesions of classic-type mycosis fungoides (MF) presented sudden ESK that were exclusively limited to the MF lesions. In conclusion, this patient combined an isotopic response and ESK.